Occurrence of multiple fistulas decades after ingestion and neglect of numerous thermometers: a case report - Katrin Schulte; Henning Wendelin Wolf (Surgical Case Reports, 2024)
Abstract Background Ingestion of thermometers is a very rare occurrence and associated with penetrations of hollow organs. An event decades ago can lead to the development of fistulas. Case presentation We present a case of a 62-year-old male who swallowed multiple thermometers with a length of up to 22 cm over a period of 40 years. Diagnostic imaging presented a retroperitoneal abscess due to a duodenal perforation of the longest thermometer as well as multiple other thermometers stuck in the small intestine. After all thermometers were removed and the abscess drained, the patient showed a clinical deterioration. In further operations we found a duodeno-sigmoid fistula and a gastro-thoracal fistula, which were not visible in the initial operations and imaging. Conclusion We recommend an active search for fistulas especially in the case of long-foregone ingestion.